Perancangan Interaksi dan Antarmuka Pengguna Sistem Informasi Penjualan Balinesia T-Shirt menggunakan Pendekatan Human Centered Design - Ni Komang Tri Puspadewi; Ismiarta Aknuranda; Yusi Tyroni Mursityo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Online shopping activities in Indonesia are now increasing rapidly. Therefore, businesses need to provide a site that allows their customers to shop online. The purpose of this study is to design an information system that can handle the online sales in Balinesia T-Shirt, which has not run optimally. The design approach used in this study is Human Centered Design (HCD), to produce a designs solutions that can meet the needs, easy to use, and provide a good experience for the users. The resulting design solution is a software-based high-fidelity prototype. The design solution is then evaluated using the usability testing technique. After the first evaluation, the design solution was improved and two alternatives were made. The second evaluation shows that the two alternatives are relatively easy to use, but there are still some improvements that need to be made to the user interface. From the user satisfaction it was found that all participants were satisfied with the design.